Isolation, identification and anti-candidal activity of filamentous fungi from Saudi Arabia soil - Nouf M. Al-Enazi; Amani S. Awaad; Monerah R. Al-Othman; Nour K. Al-Anazi; Saleh I. Alqasoumi (Elsevier, 2018)
Ten fungal strains; namely, Penicillium melinii, Petriella setifera, Aspergillus pseudo-niger, Alternaria chlamydospora, Pythium nayoroense, Phoma glomerata, Mucor ramosissimus, Mucor racemosus, Fusarium chlamydosporum and Rhizopus azygosporus were isolated from soil. The extra- and intra-cellular extracts of the fungal strains grown on malt extract and yeast-extract sucrose media were screened for their anticandidal activity against different clinically-isolated Candida species. Most of the fungal extracts showed activity against different Candida species. However, the fungal strains grew on malt extract showed greater activities than those grew on yeast extract sucrose media. The activity of the intracellular was higher than the extracellular metabolites. All fungal extracts (extra and intra) were similar in chemical constituent; they contained carbohydrates and/or glycosides, unsaturated sterols and/or triterpens, tannins and traces of coumarins. Alkaloids, flavonoids, saponins, anthraquinones and cardenolides were no detected. The intra-cellular extracts contained more compounds than the extra-cellular extracts.